Investigating the Impact of Soil pH and Texture on Legume Species Root Nodule Formation - -, Jamilah (International journal of agriculture and biology, 2025)
Nodule formation plays a pivotal role in legume plants establishing a mutualistic symbiotic relationship that can reduce the need for nitrogen fertilizer application. The objective of this study was to determine the effect of texture, soil pH and plant growth phase on the formation of root nodules of various legume species. This study, conducted in Padang City, West Sumatra. Indonesia, from January to February 2024, employed qualitative tests and observational methods to investigate the impact of soil texture, pH, and plant growth phase on root nodule formation across various legume species. Eight types of legumes served as research subjects including five wild varieties and three domestic types. At each location eight plants were sampled, enclosed in tightly sealed plastic bags with open tops and transported to the laboratory ensuring that soil moisture was maintained at field capacity. Spearman’s Rho correlation analysis established relationships between variables at the 5% significance level. Regression models were examined based on the correlation coefficient of determination (R2). The regression equation displaying the highest correlation coefficient was selected. The formation of root nodules on legume plants' roots is influenced by various soil factors. The shape of the nodule is influenced by the legume leaves' shape. Sandy loam texture produces more nodules than other soil textures. The highest number of nodules is found in the primordial phase of the flower. A soil pH close to 5 produces more nodules than lower or higher soil pH levels. Based on the multiple linear regression equation, it is known that the formation of legume root nodules will increase as root weight and soil pH increase. The formation of effective root nodules will decrease as soil pH increases beyond a certain level. In general, the number of root nodules and effective root nodules are directly proportional to soil texture. Sandy clay soil is conducive to higher nodule formation, followed by clay texture and silt loam clay. The effectiveness of nodules was nearly consistent across each soil texture but reached its peak in clay-textured soil. Sandy-textured soil produces legume plants with the highest nodule formation compared to clay soil and exhibits high levels of organic matter. Generally, sandy soil has the potential for up to twice the nodule formation compared to clay soil and six times more than organic soil. It has been demonstrated that sandy soil possesses a higher macro-pore content than clay soil. However, organic soil also has high macro-pore content, along with optimal macro pores. Despite the presence of abundant organic matter, organic soil is not capable of producing more nodules than sandy or clay-textured soil.